Resurrection plants of the genus Ramonda: prospective survival strategies – unlock further capacity of adaptation, or embark on the path of evolution? - Rakic, Tamara; Lazarevic, Maja; Jovanovic, Zivko S.; Radovic, Svetlana; Siljak-Yakovlev, Sonja; Stevanovic, Branka; Stevanovic, Vladimir (Frontiers in Plant Science, 2014)
Paleoendemic species of the monophyletic genus Ramonda (R. myconi, R. serbica and R. nathaliae) are the remnants of the Tertiary tropical and subtropical flora in Europe. They are the rare resurrection plants of Northern Hemisphere temperate zone. Ramonda serbica and R. nathaliae are chorologically differentiated in the Balkan Peninsula and occupy similar habitats in calcareous, northward slopes in canyons and mountainsides. They remain well-hydrated during spring, late autumn and even in winter. In summer and early autumn when plants are subjected to drought and thermal stress, their desiccation tolerance comes into operation and they fall into anabiosis. Investigations revealed the permanent presence of ubiquitine and its conjugates, high amounts of oxalic acid and proline. Both species are homoiochlorophyllous. It enables them to rapidly resume photosynthesis upon rehydration, but also makes them susceptible to ROS formation. Dehydration induces activation of antioxidative enzymes (APX, GR, PPO), increase in amounts of AsA and GSH, phenolic acids, dehydrins, sucrose and inorganic ions. Plasma membranes, characterized by high amount of cholesterol, are subjected to decrease in membrane fluidity mostly on account of increased level of lipid saturation. Cytogenetic analysis revealed that R. nathaliae is a diploid (2n=48) and probably evolutionary older species, while R. serbica is a hexaploid (2n=144). Two species live together in only two localities forming hybrid individuals (2n=96). Polyploidization is the major evolutionary mechanism in the genus Ramonda that together with hybridization ability indicates that these relict species which have preserved an ancient survival strategy are not the evolutionary „dead end“. The species of the genus Ramonda are promising sources of data important for understanding the complex strategy of resurrection plants’ survival, appraised through a prism of their evolutionary and adaptive potential for multiple environmental str